HUBUNGAN KEPATUHAN MENGGOSOK GIGI SEBELUM TIDUR MALAM DENGAN TERJADINYA KARIES GIGI PADA ANAK USIA SEKOLAH DASAR 7 – 12 TAHUN DI SDN 03 MADIUN LOR KOTA MADIUN - Sulistyaningrum, Ervina Maret (Journal Nursing Care and Biomolecular, 2019)
Introduction: Preliminary study showed that the 5 students who obediently brush their teeth before going to sleep at night as many as 3 students are not experience dental caries and 2 students experience dental caries. While 8 students who have not obey brush their teeth before going to sleep at night as many as 2 students not experience dental caries and 6 students experience dental caries. Methods:  The purpose of this study was to determine the relationship of compliance with brushing before going to bed with the occurrence of dental caries in elementary school age children 7-12 The research design used in this study was cross sectional. The sample in this study were 77 students. C-Square test was used to analys the data. Results and Analysis: The obedient students brushed their teeth before went to bed at night with 6 students (7.8%) and non-adherents brushing their teeth before went to bed 71 students (92.2%) while 74 students having dental caries (96.1 %) and those who did not experience dental caries 3 students (3.9%). Chi-Square statistical test obtained a value of p = 0,000 (p <? = 0.05) which means alternative hypotheses were accepted. While the results of the contingency coefficient test obtained the correlation coefficient of 0.597, which means there had relationship between adherence to brushing before going to bed with the occurrence of dental caries with sufficient correlation and parallel direction. Discuss: There is a obedience to brushing teeth before going to bed at night with the occurrence of dental caries in children aged 7 to 12 years old at 03 madiun lor, Madiun city.